Antibiotics‐induced modulation of large intestinal microbiota altered aromatic amino acid profile and expression of neurotransmitters in the hypothalamus of piglets. Issue 3 (28th June 2018) - Gao, Kan; Pi, Yu; Mu, Chun‐Long; Peng, Yu; Huang, Zan; Zhu, Wei‐Yun
Abstract: The evidence of gut microbiota‐mediated modulation of brain function has been widely recognized from studies using germ‐free rodents or animals with oral antibiotic‐induced microbiota depletion. Since the large intestine harbors greater numbers and more diverse of microbes than in the small intestine, large intestinal microbiota may play a crucial role in the modulation of brain function. In this study, a large intestinal microbiota‐targeted strategy was used to investigate the impact of large intestinal microbiota on brain function. Twelve piglets (12.08 ± 0.28 kg) fitted with a T‐cannula at the distal ileum were fed a standard diet and randomly assigned to two groups ( n = 6) for ileal infusion of either saline or antibiotics. After 25 days of infusion, ileal and fecal microbiota, serum amino acids and neurotransmitters, and hypothalamic transcriptomics were analyzed. While the antibiotic infusion did not change the proximal ileal microbial composition, it markedly altered the fecal microbial composition and increased aromatic amino acid (AAAs) metabolism ( p < 0.05), suggesting the infusion specifically targeted large intestinal microbes. Concentrations of AAAs were likewise decreased in the blood and hypothalamus ( p < 0.05) by antibiotic infusion. Antibiotic infusion further decreased concentrations of hypothalamic 5‐hydroxytryptamine (5‐HT) and dopamine, in line with AAAs being their precursors. An up‐regulation in gene expressions of neurotransmitter transporters and synthetases was observed ( q < 0.001). In conclusion, the distalileal‐antibiotic infusion altered neurotransmitter expression in the porcine hypothalamus and this effect occurred simultaneously with changes in both the large intestinal microbiota, and AAAs in the large intestine, blood and hypothalamus. These findings indirectly indicate that large intestinal microbiota affects hypothalamic neurotransmitter expressions. Read the Editorial Highlight for this article on page 208 . Abstract : The existence of gut microbiota–brain axis has been recognized. We proposed a model that the altered large intestinal microbiota induced by antibiotics, resulted in the decreased aromatic amino acids (AAAs) availability in the circulation and hypothalamus, which further hindered 5‐hydroxytryptamine (5‐HT) and dopamine biosynthesis. Our findings indirectly indicate that large intestinal microbiota affects hypothalamic neurotransmitter expression in piglets. Read the Editorial Highlight for this article on page 208 .